The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1080/00268978900102071
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of spectroscopic properties of some indium, tin and antimony compounds

Abstract: Spectroscopic properties of dimers, hydrides, oxides, fluorides and sulphides of the elements In, Sn and Sb have been calculated using energy-adjusted pseudopotentials. Results are given for bond lengths R e, dissociation energies D e, vibrational frequencies co e and dipole moments #e of the ground states.Comparison is made both with experimental and theoretical values, where available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Froben et al, 15 on the basis of Raman spectra of matrix-isolated group IIIA dimers, reported a 3 ⌺ Ϫ ground state and e ϭ118 cm Ϫ1 and as a consequence the dissociation energy quoted by Huber and Herzberg 4 (1.0 1 eV) was corrected to 0.87 eV or 84 kJ mol Ϫ1 . More recently, the theoretical investigations carried out by Balasubramanian and Li 10 and Igel-Mann et al 11 agree, as mentioned above, in quoting a 3 ⌸ ground state and in the corresponding D e values ͑1.02 and 1.09 eV, respectively͒. Balasubramanian and Li, 10 on the other hand, found the spin-orbit effect to be non-negligible for the electronic states of In 2 .…”
Section: B Insupporting
confidence: 49%
See 1 more Smart Citation
“…Froben et al, 15 on the basis of Raman spectra of matrix-isolated group IIIA dimers, reported a 3 ⌺ Ϫ ground state and e ϭ118 cm Ϫ1 and as a consequence the dissociation energy quoted by Huber and Herzberg 4 (1.0 1 eV) was corrected to 0.87 eV or 84 kJ mol Ϫ1 . More recently, the theoretical investigations carried out by Balasubramanian and Li 10 and Igel-Mann et al 11 agree, as mentioned above, in quoting a 3 ⌸ ground state and in the corresponding D e values ͑1.02 and 1.09 eV, respectively͒. Balasubramanian and Li, 10 on the other hand, found the spin-orbit effect to be non-negligible for the electronic states of In 2 .…”
Section: B Insupporting
confidence: 49%
“…Both the two theoretical investigations carried out by Balasubramanian and Li 10 and Igel-Mann et al 11 agree in finding the 3 ⌸ state to be the ground state for In 2 . In the evaluation of the thermal functions we utilized the relativistic results of Balasubramanian and Li 10 where the electronic levels including the -coupling are provided.…”
Section: Inmentioning
confidence: 53%
“…The inaccuracy of bond lengths and bond angles due to that treatment is expected to be small as demonstrated for related compounds in several earlier papers [41][42][43]. The equilibrium structures are found to be three-dimensional geometries for m >/4, i.e., a tetrahedron for m = 4, a square pyramid for m = 5 and a trigonal prisma for m = 6.…”
Section: Discussionmentioning
confidence: 93%
“…For this geometry, calculations including valance correlation were performed for the neutral Xm cluster and the singly charged ions Xm + in order to determine the atomization energies (De) and the (vertical) ionization potentials (IP). (It has been shown in recent papers [41][42][43] that there is no qualitative change in geometry between SCF and the valencecorrelated level.) In the case of the dimers )(2, additionally, vibrational frequencies to e were determined by calculating (total) valence energies at four or five points around the minimum of the potential curve (with AR e = 0-1 a0) and fitting these values to third-degree polynomials at each level of approximation.…”
Section: ~I Rai LI Ljmentioning
confidence: 94%
“…In fact, such calculations have been reported in some of the abovementioned mass spectrometric studies. 3,5 In addition, DFT and/or ab initio calculations have been performed in other spectroscopic studies of various antimony oxides in order to assist spectral assignments, 9,15 and there are also numerous independent computational studies on antimony oxides, [16][17][18][19][20][21][22] though most of these computational studies are on the diatomic antimony monoxide SbO. [16][17][18][19][20][21] To our knowledge, however, there are only two computational studies, which have considered the triatomic antimony dioxide ͑SbO 2 ͒.…”
Section: Introductionmentioning
confidence: 99%